Ukrainian food journal. Vol. 6. Issue 1 - National University of Food Technologies (My University, 2017)
International scientific periodical to publish the results of research experts in the field of food science, engineering and technology, chemistry, economics and management. Міжнародне наукове періодичне видання для публікації результатів досліджень фахівців у галузі харчової науки, техніки та технології, хімії, економіки і управління.
Keywords: food technologies; biotechnology; microbiology; food chemistry; processes and equipment of food productions; харчові технології; біотехнологія; мікробіологія; харчова хімія; процеси і апарати харчових виробництв; пищевые технологии; биотехнология; микробиология; пищевая химия; процессы и аппараты пищевых производств